Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

well I had this equation at the begining

$$ i \frac{\partial u}{\partial{z}} + \frac{1}{2 k_0} \frac{\partial^2 u}{\partial x^2} +\frac{1}{2}k_0 n_1 F(z) x^2 u-\frac{i[g(z) -\alpha(z)]}{2}u + k_0 n_2|u|^2 u = 0, $$

If I substitute $X=x/w_0$, $Z=z/L_D$, $G=(g(z)-\alpha(z))L_D$, $U=u\sqrt{k_o n_2 L_D}$, $L_D=k_0w_0^2$ $w_0=(k_0^2n_1)^{-1/4}$

I am not getting this equation

$$ i\frac{\partial U}{\partial Z} + \frac{1}{2} \frac{\partial^2 U}{\partial X^2} + F(Z) \frac{X^2}{2} U - \frac{i}{2} G(Z) U + |U|^2 U = 0 $$

but getting 2nd term multiplied with $w_0$, could any one tell me am I right or wrong? I must say I have calculated it 3 times. please help. well replace $f(z)$ by $F(Z)$ and $g(z)$ by $G(Z)$

share|improve this question
    
In the first equation, $F(z)$ should be $f(z)$. Sorry for the bad edit. –  Pragabhava Nov 3 '12 at 18:56

1 Answer 1

up vote 1 down vote accepted

Lets see. Taking the change of variables $X = \frac{x}{w_0}$, $Z = \frac{z}{L_D}$ and $U = \frac{u}{C}$, we have

\begin{align} \frac{\partial}{\partial x} &= \frac{\partial X}{\partial x}\frac{\partial}{\partial X} = \frac{1}{w_0}\frac{\partial}{\partial X},\\ \frac{\partial^2}{\partial x^2} &= \frac{1}{w_0^2}\frac{\partial}{\partial X},\\ \frac{\partial}{\partial z} &= \frac{\partial Z}{\partial z}\frac{\partial}{\partial Z} = \frac{1}{L_D}\frac{\partial}{\partial Z}. \end{align}

Substituting into the equation,

\begin{multline} \frac{i}{C L_D} \frac{\partial U}{\partial Z} + \frac{1}{2 C k_0 w_0^2} \frac{\partial^2 U}{\partial x^2} + \frac{w_0^2 k_0 n_1}{2 C} f(L_D Z) X^2 U \\ - \frac{i \big[g(L_D Z) - \alpha(L_D Z)\big]}{2 C} U + \frac{k_0 n_2}{|C|^2 C} |U|^2 U = 0. \end{multline}

Multiplying by $C L_D$ the hole equation,

\begin{multline} i \frac{\partial U}{\partial Z} + \frac{L_D}{2 k_0 w_0^2} \frac{\partial^2 U}{\partial x^2} + \frac{w_0^2 k_0 n_1 L_D}{2} f(L_D Z) X^2 U \\ - \frac{i L_D\big[g(L_D Z) - \alpha(L_D Z)\big]}{2} U + \frac{k_0 n_2 L_D}{|C|^2} |U|^2 U = 0. \end{multline}

Taking $L_D = k_0 w_0^2$,

\begin{multline} i \frac{\partial U}{\partial Z} + \frac{1}{2} \frac{\partial^2 U}{\partial x^2} + \frac{w_0^4 k_0^2 n_1}{2} f(k_0 w_0^2 Z) X^2 U \\ - \frac{i k_0 w_0^2\big[g(k_0 w_0^2 Z) - \alpha(k_0 w_0^2 Z)\big]}{2} U + \frac{k_0^2 w_0^2 n_2}{|C|^2} |U|^2 U = 0. \end{multline}

Let $w_0 = (k_0^2 n_1)^{-1/4}$, then $L_D = \frac{1}{\sqrt{n_1}}$ and

\begin{multline} i \frac{\partial U}{\partial Z} + \frac{1}{2} \frac{\partial^2 U}{\partial x^2} + \frac{1}{2} f(n_1^{-1/2} Z) X^2 U \\ - \frac{i \big[g(n_1^{-1/2} Z) - \alpha(n_1^{-1/2} Z)\big]}{2 \sqrt{n_1}} U + \frac{k_0 n_2}{\sqrt{n_1} |C|^2} |U|^2 U = 0. \end{multline}

Taking $C = \frac{\sqrt{k_0 n_2}}{n_1^{1/4}} = \sqrt{k_0 n_2 L_D}$,

\begin{multline} i \frac{\partial U}{\partial Z} + \frac{1}{2} \frac{\partial^2 U}{\partial x^2} + \frac{1}{2} f(n_1^{-1/2} Z) X^2 U \\ - \frac{i \big[g(n_1^{-1/2} Z) - \alpha(n_1^{-1/2} Z)\big]}{2 \sqrt{n_1}} U + |U|^2 U = 0. \end{multline}

Denoting \begin{align} F(Z) &= f\left(\tfrac{Z}{\sqrt{n_1}}\right),\\ G(Z) &= \frac{1}{\sqrt{n_1}}\left[g\left(\tfrac{Z}{\sqrt{n_1}}\right) - \alpha\left(\tfrac{Z}{\sqrt{n_1}}\right)\right] \end{align}

we have $$ i \frac{\partial U}{\partial Z} + \frac{1}{2} \frac{\partial^2 U}{\partial x^2} + \frac{1}{2} F(Z) X^2 U - \frac{i}{2} G(Z) U + |U|^2 U = 0. $$

What we have done here is written the original equation in adimensional form. Judging by the form of the equation, $L_D$ has [time] dimensions, $w_0$ has [space] dimesions, and $u$ has [space/time²] dimensions.

Please doublecheck the math.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.